PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAAN PELANGGAN PADA PERUSAHAAN DAERAH AIR MINUM (PDAM) TIRTA KANDILO KABUPATEN PASER - Latte, Jumai (Inovatif Jurnal Administrasi Niaga, 2019)
The research is done at PDAM of PDAM Tirta Kandilo Kabupaten Paser with the objectives 1) to find the effect of tangible 2) to find the effect of reliabilty. 3) to find the effect responsines. 4) to find the effect of assurance. 5) to fine the effect of emphaty on the custumer’s satisfaction. The Types of research is explanatory research. Total respondents taken are 100 respondents, the sample determined by using nonprobability sampling, namely through accidental sampling. The analysis data technique in this research use SEM analysis which software Smart PLS version 2.0 M3. These results showed that 1) Tangible no significant effect on the custumer’s satisfaction with the effect of 2,5% 2) Reliability no significant effect on the custumer’s satisfaction with the effect of 9,9%. 3) Responsivenes no significant effect on the custumer’s satisfaction with the effect of 10,2%. 4) Assurance no significant effect on the custumer’s satisfaction with the effect of 2,7%. But 5) Empaty significant effect on the custumer’s satisfaction with the effect of 91,4%.